Corrosion of Carbon Steel in Mauritian water bodies - Seechurn,Yashwantraj (2022)
ABSTRACT Carbon steel is a commonly used metal in water applications in Mauritius. However, the corrosion resistance of steels and effectiveness of corrosion prevention methods in Mauritian water bodies are unknown. This study is performed to investigate the corrosion behavior of S235 carbon steel in the local tropical waters using various corrosion monitoring techniques. Specimens of the metal are subjected to a simple laboratory immersion test under ambient conditions according to ASTM G31. The coupons are immersed in three distinctively different waters. Upon removal after specific time intervals over a 3-month period, the mass loss, thickness loss and surface roughness are duly evaluated. Mass loss and thickness loss variation with time of immersion are obtained in the form of the power law function. Regarding the surface roughness parameters measured, it is observed that they change logarithmically with corrosion loss due to increasing thickness of the rust layer. A general deterministic model in terms of Rp and Rq is successfully stemmed using Genetic Programming to forecast the corrosion rate.